The reliability and construct validity of the functional threshold power test in trained cyclists - Gough, L.; Dobson, B.; Williams, J.; Downes, G.; Sturridge, S.; Warner, A.; Sparks, A.; Brown, D. (Journal of Science and Cycling, 2025)
The functional threshold power (FTP) 20-min test (FTP20) is popular amongst cyclists and coaches due to the theory it can predict the power output that can be sustained for 60-mins. However, little is known in terms of the reliability and validity of this construct, therefore the aim of this study was to assess the reliability of the FTP20 test and the construct validity of this test to predict 60-min power. Twenty-two male trained cyclists (age = 32 ± 10 years, body mass (BM) = 77.2 ± 6.8 kg, maximal oxygen uptake (VO2max) = 59.4 ± 5.6 ml.kg-1.min-1 BM) completed five trials consisting of a VO2max test, a familiarisation trial of the FTP20, two experimental FTP20 tests, and a time to volitional exhaustion (TLIM) at 95% FTP20. The repeatability for mean power output (MPO) during the FTP20 was excellent (r = 0.94, CI 0.82, 0.98, p<0.001). Mean TLIM (at 95% FTP20) was 42 ± 17-min, with six participants within 10-min of the 60-min suggested threshold. These results suggest that the FTP20 is reliable, however it does not predict 60-min power with a high level of validity. Future research should explore adapting the calculation of FTP whereby the intensity may be lowered (i.e., 80-90% MPO of FTP20), particularly as most participants` TLIM was far below the suggested 60-min time frame.